2023
DOI: 10.3390/ijms24076771
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Structural Alerts in Marketed Drugs for Improving Adverse Outcome Pathway Framework of Drug-Induced QT Prolongation

Abstract: In pharmaceutical treatment, many non-cardiac drugs carry the risk of prolonging the QT interval, which can lead to fatal cardiac complications such as torsades de points (TdP). Although the unexpected blockade of ion channels has been widely considered to be one of the main reasons for affecting the repolarization phase of the cardiac action potential and leading to QT interval prolongation, the lack of knowledge regarding chemical structures in drugs that may induce the prolongation of the QT interval remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Annotations with complete attention maps are provided in Supplementary File S1. The table reveals that MoLFormer-XL was used to report SAs associated with DIQT in previous studies, such as amines, ethers, and aromatic halogens [13]. Furthermore, Aniline structures, such as pyridine in disopyramide phosphate and the benzimidazole ring in quinidine gluconate and vandetanib, were also identified as crucial structural features associated with DIQT [38][39][40].…”
Section: Attention Analysis For Drugs With a High Risk Of Diqtmentioning
confidence: 96%
See 4 more Smart Citations
“…Annotations with complete attention maps are provided in Supplementary File S1. The table reveals that MoLFormer-XL was used to report SAs associated with DIQT in previous studies, such as amines, ethers, and aromatic halogens [13]. Furthermore, Aniline structures, such as pyridine in disopyramide phosphate and the benzimidazole ring in quinidine gluconate and vandetanib, were also identified as crucial structural features associated with DIQT [38][39][40].…”
Section: Attention Analysis For Drugs With a High Risk Of Diqtmentioning
confidence: 96%
“…We compared the performance of our proposed MoLFormer-XL-CNN model with state-of-the-art methods reported in previous studies (Figure 1). In previous studies, Wulin Long et al indicated that SVM achieved the highest MCC value and recall rate (mean MCC = 0.591, mean recall rate = 0.870), predicting the high risk of inducing QT interval prolongation of marketed drugs [13]. Liyuan Kang et al indicated that SVM performed better in detecting the marketed drugs with high teratogenic risk (mean MCC = 0.312) [12].…”
Section: Model Performance On Three Curated Datasetsmentioning
confidence: 99%
See 3 more Smart Citations